2002
DOI: 10.5194/aab-45-481-2002
|View full text |Cite
|
Sign up to set email alerts
|

Genetische Beziehungen für das Merkmal Lebenstagszunahme in einem Dreirassenkreuzungsprogramm beim Schwein

Abstract: Abstract. Title of the paper: Genetic association for daily gain (lifetime) in an crossbreeding program The aim of this investigation is an analysis of the crossing structure of a three-race crossing program and the genetic relations with respect to the trait average daily gain. For this purpose we examine the genetic relations for their usefulness for a estimation of genetic parameters and breeding values. Finally a parameter estimation is carried out. The data basis consists of 1757 German Large White perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…These findings suggest that though meat quality is internationally considered an important trait to be improved by genetic selection its definition may not be optimal. Valuable cuts and proportion of valuable cuts both showed moderately high heritabilities and were in accordance with the reported estimates of others (GROENEVELD et al, 1998;GROENEVELD and PESCOVICOVA, 1999;WOLF et al, 2001;SCHULZE et al, 2001;FISCHER et al, 2002). The other traits measured in the station test (DOT, FEED, NDG, FCR) showed moderate heritabilities and were similar to the findings of CHEN et al 2002; DUCOS et al (1992); ZHANG et al 2000for DOT;GROENEVELD et al (1996) for FEED; but were higher than reported by HERMESCH et al 2000, HOFER et al, (1992) and MRODE and KENNEDY (1993) for NDG, FCR.…”
Section: Resultssupporting
confidence: 92%
“…These findings suggest that though meat quality is internationally considered an important trait to be improved by genetic selection its definition may not be optimal. Valuable cuts and proportion of valuable cuts both showed moderately high heritabilities and were in accordance with the reported estimates of others (GROENEVELD et al, 1998;GROENEVELD and PESCOVICOVA, 1999;WOLF et al, 2001;SCHULZE et al, 2001;FISCHER et al, 2002). The other traits measured in the station test (DOT, FEED, NDG, FCR) showed moderate heritabilities and were similar to the findings of CHEN et al 2002; DUCOS et al (1992); ZHANG et al 2000for DOT;GROENEVELD et al (1996) for FEED; but were higher than reported by HERMESCH et al 2000, HOFER et al, (1992) and MRODE and KENNEDY (1993) for NDG, FCR.…”
Section: Resultssupporting
confidence: 92%